Acid sphingomyelinase deficiency: The clinical spectrum of 2 patients who carry the Q294K mutation and diagnostic challenges - Ulrike Blümlein; Eugen Mengel; Yasmina Amraoui (Molecular Genetics and Metabolism Reports, 2022)
Acid sphingomyelinase deficiency (ASMD) is caused by pathogenic variants in the SMPD1 gene. This chronic, progressive, and potentially fatal condition requires prompt specialist care. The diagnosis of ASMD can be delayed or missed if patients that harbor the Q294K mutation undergo enzyme activity assessments that employ synthetic fluorometric substrates. Two case studies are presented, which illustrate the spectrum of disease in patients with a compound heterozygous Q294K pathogenic variant and the impact of false normal ASM activity results.